PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN PROSES SAINS DAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA - Meida Warohmah; Avini Martini; Fajar Kusumah Solihin (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research is motivated by the low skill of the science process and the ability to think critically by students, because science is seen as difficult, thus affecting learning outcomes. One of the things that is done is to implement the PBL model. PBL combines initial knowledge and new to learn critical thinking and problem-solving skills, so researchers formulate problems, is there any influence of the PBL model on science process skills and critical thinking ability between before and after the use of the PBL model. This study aims to determine the influence on science process skills and critical thinking skills before and after the use of the PBL model. Method with pre-experimental form One–group Pretest-posttest. The population taken was 10 students. Data collection by observation and tests. Based on observations, an overall average of 84 was obtained and the distribution scale was almost entire. So, there is an almost entire influence on students' science process skills using the PBL model. Based on the calculation, a value of -2,228 ≥-3,6 ≤ 2.228, so H0 is rejected and HI is accepted. So, there is noinfluence on the ability to think critically between before and after using the PBL model.